Pengaruh Pajak Hotel, Restoran dan Restribusi Daerah terhadap Pendapatan Asli Daerah Atau Provinsi Sumatera Utara Periode 2019-2021 (Lembaga Pengembangan Kinerja Dosen, 2025)
The problem in this research is that regional original income from data for the last 3 years has not been realized or reached the predetermined target. The aim of this research is to determine the effect of hotel, restaurant taxes and regional levies on the original regional income of districts and cities in North Sumatra Province for the 2019-2021 period. The population of this research is all districts and cities in North Sumatra Province for the 2019-2021 period. The sampling technique used was saturated sampling (census) with a total sample of 99 consisting of 33 districts and cities with a research year of 3 years. The data analysis technique uses multiple linear regression analysis. The research results show that (1) hotel tax has a positive and significant effect on local original income. (2) restaurant tax has a positive and significant effect on local original income (3). Regional levies have a positive and significant effect on local original income (4) hotel tax, restaurant tax and regional levies simultaneously influence local original income. (5) the contribution of all variables to local original income is 76.5% while the remaining 23.5% is influenced by other variables not examined in this research.